2006
DOI: 10.1002/glia.20409
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1‐infected and/or immune activated macrophages regulate astrocyte SDF‐1 production through IL‐1β

Abstract: Stromal cell-derived factor 1 alpha (SDF-1alpha) and its receptor CXCR4 play important roles in the pathogenesis of human immunodeficiency virus type one (HIV-1)-associated dementia (HAD) by serving as a HIV-1 co-receptor and affecting cell migration, virus-mediated neurotoxicity, and neurodegeneration. However, the underlying mechanisms regulating SDF-1 production during disease are not completely understood. In this report we investigated the role of HIV-1 infected and immune competent macrophage, the princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 67 publications
4
87
0
Order By: Relevance
“…HIF-1 and VEGF enhance the expression of CXCR4 in glioblastoma (Zagzag D et al, 2006). IL-1β induces CXCL12 in astrocytes by ERK and PI3K signaling pathways (Calderon TM et al, 2006;Peng H et al, 2006). Our lab demonstrated that CXCR4 expression by primary mouse astrocytes is suppressed by exposure to TNF-α (Han Y et al, 2001a).…”
Section: Inducible Expressionmentioning
confidence: 72%
See 2 more Smart Citations
“…HIF-1 and VEGF enhance the expression of CXCR4 in glioblastoma (Zagzag D et al, 2006). IL-1β induces CXCL12 in astrocytes by ERK and PI3K signaling pathways (Calderon TM et al, 2006;Peng H et al, 2006). Our lab demonstrated that CXCR4 expression by primary mouse astrocytes is suppressed by exposure to TNF-α (Han Y et al, 2001a).…”
Section: Inducible Expressionmentioning
confidence: 72%
“…CXCL12 can be briefly up-regulated under some pathathological situations such as HIV 1-asociated dementia, brain tumor, ischemia (stroke) and Neuroinflammation (Rempel SA et al, 2000;Rostasy K et al, 2003;Hill WD et al, 2004;Metelitsa LS et al, 2004;Miller JT et al, 2005;Peng H et al, 2006;Tabatabai G et al, 2006). Astrocytes and vascular endothelial cells in the parenchyma have been suggested as two primary cell sources for inducible CXCL12.…”
Section: Inducible Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…siRNA knockdown of glutaminase siRNA knockdown in NPCs was performed, as previously described [28]. Briefly, siRNA targeting GLS1 (ID# s5840) was purchased from Applied Biosystems, Inc. (Foster City, CA).…”
Section: Human Npc Differentiationmentioning
confidence: 99%
“…During development of the DG and neocortex, CXCR4 is expressed by migrating NPC and neuronal precursors, and CXCL12 is expressed by cells lining the migratory path and endpoint of migration (McGrath et al 1999;Lu et al 2002;Stumm et al 2003). Previous studies have indicated that astrocytes, neurons, and NPC express CXCL12, but astrocytes seem to be the major cell type of neural lineage expressing high levels of CXCL12 (Zheng et al 1999;Langford et al 2002;Rostasy et al 2003;Peng et al 2006). The spatial and cellular expression pattern of CXCL12 and CXCR4 in the brain is consistent with their role in regulating the migration and possibly, as is the case with cerebellar granule cells, the proliferation of neuronal and progenitor cells.…”
Section: Introductionmentioning
confidence: 99%